Clinical outcomes of surgical and imatinib treatment for rectal gastrointestinal stromal tumours: retrospective cohort study. Issue 3 (20th May 2022) - Tsukamoto, Shunsuke; Honma, Yoshitaka; Shoji, Hirokazu; Hirano, Hidekazu; Inoue, Manabu; Takamizawa, Yasuyuki; Moritani, Konosuke; Imaizumi, Jun; Kanemitsu, Yukihide
Abstract: Background: Rectal gastrointestinal stromal tumours (GISTs) are rare and treated mainly by radical surgery. Although the importance of perioperative imatinib has been recognized, there are few reports on its outcomes. Method: Consecutive patients diagnosed with rectal GISTs between July 2008 and February 2021 were identified from a prospective database. Effects of perioperative imatinib were investigated, and surgical and survival outcomes were compared between neoadjuvant imatinib and upfront surgery. Results: 34 patients meeting the inclusion criteria were identified. Compared with upfront surgery (n = 11), the neoadjuvant imatinib group (n = 23) had significantly larger tumours (median size 8.3 versus 2.5 cm; P = 0.01) and included a significantly greater proportion of high-risk patients according to the modified Fletcher classification (20/23 (87.0%) versus 6/11 (54.5%); P = 0.02). Comparing the operation planned based on imaging before neoadjuvant imatinib and the operation performed, there was an increase in sphincter-preserving surgery (4/23 (17.4%) to 11/23 (47.8%); P = 0.02), abdominoperineal resection 11/23 (47.8%) reduced to 7/23 (30.4%); P = 0.13) and total pelvic exenteration reduced from 8/23 (34.8%) to 5/23 (21.7%); P = 0.01). Tumours were downsized by a median of 30 per cent (range 0 per cent to −56 per cent; P =  0.01). During follow-up (median 42, range 5–131 months), there was no postoperative recurrence in 29 patients who received perioperative imatinib. One of the five patients who underwent surgery without neoadjuvant or adjuvant imatinib developed local recurrence. Conclusion: Treatment with imatinib for rectal GISTs seems to improve outcomes, and neoadjuvant imatinib increases the rate of sphincter-preserving surgery. Abstract : Effects of perioperative imatinib for rectal gastrointestinal stromal tumours (GISTs) were investigated, and surgical and survival outcomes were compared between neoadjuvant imatinib and upfront surgery. Multidisciplinary treatment with imatinib for rectal GISTs is very useful for improving oncological outcome, and neoadjuvant imatinib enables function-preserving surgery.